Analisa Keandalan Jaringan Wireless Point To Point BMKG Stasiun Meteorologi Pekanbaru Menggunakan Metode Distribusi Weibull - Erick Justin Sanjaya; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Reliability is the ability of a system or component to perform required function over a specific time period. Reliability wireless point-point network on BMKG Meteorology Station in Pekanbaru determined from its quantitative and qualitative failure rate. This paper presents analysis of wireless point-point network reliability based on the value of MTTF. Quantitative failure such as damage of network device and qualitative failure such as failure time traffic on transmission network. The method to analyze this network reliability is weibull distribution method, by using analysis of LSM calculation. The calculation result of shape parameter value (ᶿ) quantitative and qualitative failure are 2.4554 and 2.7428 beside it value of scale parameter (α) quantitative and qualitative failure are 1.4018 and 1.3420. Quantitative and qualitative failure MTTF from during 0.1072 years and 0.0629 weeks. Value of reliability total is 0.9829.Keyword: Reliability, Weibull Distribution, MTTF.